Analysis of Cashless Transaction Behavior With Maqashid Syariah Approach - M. Riswan Azifi; Nurbaiti; Budi Dharma (Yayasan Riset dan Pengembangan Intelektual, 2023)
Cashless transactions are a trend in mature economic activity. This phenomenon is analyzed using the maq ashid sharia approach in the perspective of al-dharuriyyat al-khams , with the aim of seeing its relevance to sharia economics. The research uses a qualitative approach, with a systematic literature review method. The results of the research exploration are the findings that the use of cashless is in line with the concept of maqashid sharia in Islamic law, meaning that in essence the use of this feature is important to use, but considering the changes in the digital era that are so massive, changing the consumption behavior of people who tend to be consumptive, it is based on maqashid sharia on the five principles of maintaining al- -dharuriyyat al-khams, namely safeguarding religion, soul, mind, lineage and property, it is clear that a Muslim must try to protect his assets in transactions using non-cash . in order to maintain assets/malls which in the study of maqashid sharia are included as one of the dharuriyah al-khamsah that must be maintained.